Energetics of Li+ Coordination with Asymmetric Anions in Ionic Liquids by Density Functional Theory - Penley, Drace; Vicchio, Stephen P.; Getman, Rachel B.; Gurkan, Burcu (Frontiers in Energy Research, 2021)
The energetics, coordination, and Raman vibrations of Li-solvates in ionic liquid (IL) electrolytes are studied with density functional theory (DFT). Li+ coordination with asymmetric anions of cyano(trifluoromethanesulfonyl)imide ([CTFSI]) and (fluorosulfonyl)(trifluoro-methanesulfonyl)imide (FTFSI]) are examined in contrast to their symmetric analogues of bis(trifluoromethanesulfonyl)imide ([TFSI]), bis(fluorosulfonyl)imide ([FSI]) and dicyanamide ([DCA]). The dissociation energies that can be used to describe the solvation strength of Li+ are calculated on the basis of the energetics of the individual components and the Li-solvate. The calculated dissociation energies are found to be very similar for Li+-[FTFSI], Li+-[TFSI], and Li+-[FSI] where only Li+-O coordination exists. Increase in asymmetry and anion size by fluorination on one side of the [TFSI] anion does not result in significant differences in the dissociation energies. On the other hand, with [CTFSI], both Li+-O and Li+-N coordination are present and Li-solvate has smaller dissociation energy in comparison to the solvation by [DCA] alone, [TFSI] alone, or a 1:1 mixture of [DCA]/[TFSI] anions. This finding suggests that the Li+ solvation can be weakened by asymmetric anions that promote competing coordination environments through enthalpic effects. Among the possible Li-solvates of (Li[CTFSI]n)-(n-1) , where n= 1, 2, 3 or 4, (Li[CTFSI]2)-1 is found to be the most stable with both monodentate and bidentate bonding possibilities. Based on this study, we hypothesize that the partial solvation and weakened solvation energetics by asymmetric anions may increase structural heterogeneity and fluctuations in Li-solvates in IL electrolytes. These effects may further promote Li+ hopping transport mechanism in concentrated and multicomponent IL electrolytes that is relevant to Li-ion batteries.